The ABC of handover: a qualitative study to develop a new tool for handover in the emergency department. - Farhan, M; Brown, R; Woloshynowych, M; Vincent, C (2012)
OBJECTIVES: This study identifies best practice for shift handover and introduces a new tool used to hand over clinical and operational issues at the end of a shift in the emergency department (ED). METHODS: Literature review, semi-structured interviews and observations of handover were used to develop a standardised process for handover. Participants were ED middle grades, consultants and senior nurses. Interviews were used to identify agreed best practice and derive a tool to classify the information into relevant sections. RESULTS: Interviews identified a variety of perceived current deficits in handover including a lack of standardised practice and structure. Participants provided examples of poor handover that were thought to have led to adverse events; these included delay in investigations and treatment for patients who were handed over with brief or inaccurate information. There was wide variation in the understanding of the meaning and purpose of shift handover, and differences were apparent according to the level of experience of the middle grades interviewed. The experts' responses were used to reach a unifying 'best practice' for the content of handover. This was then grouped under ABCDE headings to develop the ABC of handover tool. CONCLUSIONS: A simple tool was developed to provide the basis for medical shift handover, which includes clinical and operational information necessary for efficiency and organisation of the next shift. The ABC of handover classifies shift information to be handed over under the ABCDE headings, which are easy to remember and highly relevant to emergency medicine.